Opening address - Persaud, Yesu (CCS GeorgetownGY, 1993)
Suggests that the barriers to real free trade in CARICOM should be removed as in the case of Guyana. Advocates that there should be a strong and vigorous CARICOM, with the private sector playing their part, when thetime comes to negotiate with NAFTA. Posits that CARICOM countries should get about the serious business of manufacturing goods; services, and regional structures which are efficient and effective, with the greatest expendiency.